ChemInform Abstract: Metal and Base‐Free Synthesis of Arylselanyl Anilines Using Glycerol as a Solvent. Issue 3 (January 2015) - Thurow, S.; Penteado, F.; Perin, G.; Jacob, R. G.; Alves, D.; Lenardao, E. J.
Abstract The reaction is conducted under environmentally benign conditions, using the non‐toxic, low volatile, renewable glycerol as solvent.